2017
DOI: 10.1021/acsami.7b09181
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Studies of Solid Electrolyte Interphase (SEI) Formation on Crystalline Carbon Surfaces by Neutron Reflectometry and Atomic Force Microscopy

Abstract: The solid electrolyte interphase (SEI) is a complex and fragile passivation layer with crucial importance for the functionality of lithium-ion batteries. Due to its fragility and reactivity, the use of in situ techniques is preferable for the determination of the SEI's true structure and morphology during its formation. In this study, we use in situ neutron reflectometry (NR) and in situ atomic force microscopy (AFM) to investigate the SEI formation on a carbon surface. It was found that a lithium-rich adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 34 publications
5
58
0
Order By: Relevance
“…As a consequence, the observed surface morphology will induce mainly a frequency decrease. In support of our analysis, morphological characterisation of SEI layers by means of neutron reflectometry and AFM revealed that the SEI formed in 1 M LiPF 6 , EC:DEC has a very low roughness reaching 10 nm . Under these circumstances the trapped liquid in the layer cavities moves in phase with the quartz crystal and therefore performs as a rigid mass .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As a consequence, the observed surface morphology will induce mainly a frequency decrease. In support of our analysis, morphological characterisation of SEI layers by means of neutron reflectometry and AFM revealed that the SEI formed in 1 M LiPF 6 , EC:DEC has a very low roughness reaching 10 nm . Under these circumstances the trapped liquid in the layer cavities moves in phase with the quartz crystal and therefore performs as a rigid mass .…”
Section: Resultssupporting
confidence: 80%
“…These structural features are already confirmed by neutron refractometry and AFM studies. Steinhauer et al., for instance, demonstrate that SEI formed in reference electrolyte has a layer average roughness of only 10 nm . Contrary, the SEI formation in DPOP is characterized by a significant damping increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1979 a multitude of experimental SEI research has been performed [4,18], recent examples include battery storage at various state-of-charge (SoC) [12,13], differential capacity analysis during cycling [19], neutron reflectometry [20], atomic force microscopy [21], nuclear magnetic resonance [22], redox shuttles [23,24], fourier-transform infrared spectroscopy [25], and photo-electron spectroscopy [26]. As a consequence, there is a general understanding of SEI composition and morphology for few specific systems.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3a shows the first two cycles of charge/discharge profiles for Al 2 O 3 /PGM-5 and PGM-T at a current density of 0.1 A g −1 between 0.005-3 V versus Na/Na + . [56][57][58][59] It is noted that the Al 2 O 3 /PGM-5 has a much lower peak intensity than PGM-T, indicating that the decomposition of NaOTf is suppressed. In the CV profiles in Figure 3b, there is an irreversible broad cathodic peak between 0.3 and 1.0 V during the first cycle, which is due to the continuous decomposition of aprotic solvent (diglyme) and conductive electrolyte sodium salt (NaCF 3 SO 3 ) to form a protective SEI.…”
mentioning
confidence: 99%